Analisis Kinerja Keuangan PT Gresik Migas (BUMD) - Siska Eva Yuliana (JURNAL EKOBIS DEWANTARA, 2022)
This study aims to determine the financial performance of PT Gresik Migas by using secondary data in the form of financial statements from PT Gresik Migas from 2019 to 2021. The method in this study uses observation methods and literature studies. Ratio Analysis is an analytical method used in the analysis of financial statement data, and the results are taken based on the company's financial performance. The Liquidity, Solvency, Profitability, and Activity Ratios are the ratios used. The results of the ratio calculation show that the company has a fairly good operational performance in terms of Liquidity, Solvency, and Activity Ratios. But it is very good in terms of profitability ratio.